Biotechnological potential of yeast isolates from cachaça: the Brazilian spirit. (1st February 2015) - da Conceição, Luís Eduardo Fernandes Rodrigues; Saraiva, Margarete Alice Fontes; Diniz, Raphael Hermano Santos; Oliveira, Juliana; Barbosa, Gustavo Dimas; Alvarez, Florencia; da Mata Correa, Lygia Fátima; Mezadri, Hygor; Coutrim, Mauricio Xavier; Afonso, Robson José de Cássia Franco; Lucas, Candida; Castro, Ieso Miranda; et al.
Abstract: This study identified phenotypic traits appropriate for biotechnological applications of 118 yeasts isolated from cachaça distilleries. Different properties were verified: capacity to use alternative carbon sources; ability to tolerate high concentrations of sucrose, ethanol, methanol, aluminum and zinc as well as different pH values and foam production. Pichia guilliermondii and Pichia anomala strains were identified as the most promising ones for application in the second-generation biofuel industry, showing ability to grow on high glycerol concentrations. Other isolates, identified as Saccharomyces cerevisiae, produced bioethanol comparable to the industrial strains, and were therefore ideal for use in the first-generation ethanol industry. Some of these strains also showed high resistance to aluminum, as observed in sugarcane juice, and to inter-cycle washings with diluted sulphuric acid, as performed in the industrial bioethanol production process. In summary, yeast isolates from cachaça distilleries displayed robustness and phenotypic plasticity, which makes them interesting for biotechnological applications.